Flow visualisation of the external flow from a converging slot-hole film-cooling geometry - Sargison, J; Oldfield, M; Guo, S; Lock, G; Rawlinson, A (Springer, 2005)
This paper presents flow visualisation experiments for novel film-cooling hole, the converging slot-hole or console for short. Previously published experimental results have demonstrated that the console improved both the heat transfer and the aerodynamic performance of turbine vane and rotor blade cooling systems. Flow visualisation data for a row of consoles were compared with that of cylindrical and fan-shaped holes and a slot at the same inclination angle of 35° to the surface, on a large-scale, flat-plate model at engine-representative Reynolds numbers in a low speed tunnel with ambient temperature mainstream flow. In the first set of experiments, the flow was visualised by using a fine nylon mesh covered with thermochromic liquid crystals, allowing the measurement of gas temperature contours in planes perpendicular to the flow. This data demonstrated that the console was similar to a slot film, and remained thin and attached to the surface for the coolant-to-mainstream momentum flux ratios of 1.1 to 40 and for a case with no crossflow (infinite momentum flux ratio). A second set of flow visualisation experiments using water/dry-ice fog have confirmed these results and have shown that the flow through all coolant geometries is unsteady.